Pengaruh Metode Peer Practice dengan Media Kartu Kanji terhadap Motivasi dan Prestasi Belajar Mahasiswa Sastra Jepang FIB UNAIR (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2014)
Lack of ability to learn kanji will affect learning Japanese in general. To resolve this problem innovations in teaching kanji are needed, one of them is peer practice with kanji card media. This article describes how peer kanji used in teaching practice and whether this method is correlated with an increase in motivation and achievement in learning kanji of Japanese literature student in Airlangga University Faculty of Humanities. Furthermore this article also gives advice in implementing peer practice in teaching kanji.